Establishing Social Dialog between Buildings and Their Users. Issue 17 (21st October 2019) - Khashe, Saba; Lucas, Gale; Becerik-Gerber, Burcin; Gratch, Jonathan
ABSTRACT: Behavioral intervention strategies have yet to become successful in the development of initiatives to foster pro-environmental behaviors in buildings. In this paper, we explored the potentials of increasing the effectiveness of requests aiming to promote pro-environmental behaviors by engaging users in a social dialog, given the effects of two possible personas that are more related to the buildings (i.e., building vs. building manager). We tested our hypotheses and evaluated our findings in virtual and physical environments and found similar effects in both environments. Our results showed that social dialog involvement persuaded respondents to perform more pro-environmental actions. However, these effects were significant when the requests were delivered by an agent representing the building. In addition, these strategies were not equally effective across all types of people and their effects varied for people with different characteristics. Our findings provide useful design choices for persuasive technologies aiming to promote pro-environmental behaviors.